2018
DOI: 10.24843/eja.2018.v23.i02.p30
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Religiusitas, Status Sosial Ekonomi Dan Love of Money Pada Persepsi Etis Mahasiswa Akuntansi

Abstract: Penelitian ini bertujuan untuk meneliti pengaruh religiusitas, status sosial ekonomi dan love of money pada persepsi etis mahasiswa akuntansi. Teori Motivasi digunakan untuk menjelaskan hubungan antar variable. Populasi penelitian adalah seluruh mahasiswa aktif program studi akuntansi non reguler angkatan 2014 Fakultas Ekonomi dan Bisnis Universitas Udayana dengan jumlah 187 orang. Sampel penelitian berjumlah 127 orang dengan menggunakan rumus Slovin. Penelitian menggunakan teknik analisis berganda. Data dikum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
2
9
1
6
Order By: Relevance
“…The results of this study are not incompatible with research conducted by Pemayun and Budiasih [8] which states that religiosity has a positive effect on the ethical perceptions of accounting students.…”
Section: The Effect Of Religiosity On Ethical Perceptions Of Accoucontrasting
confidence: 72%
See 4 more Smart Citations
“…The results of this study are not incompatible with research conducted by Pemayun and Budiasih [8] which states that religiosity has a positive effect on the ethical perceptions of accounting students.…”
Section: The Effect Of Religiosity On Ethical Perceptions Of Accoucontrasting
confidence: 72%
“…It is also in accordance with Maslow's motivation theory which explains that humans have 5 basic needs that must be met. In its fulfilment mostly involves the need for money which has an impact on excessive love for money [8]. So, it can be concluded that where students who have high love of money will have low ethical perceptions.…”
Section: A the Influence Of Love Of Money On Ethical Perceptions Of mentioning
confidence: 99%
See 3 more Smart Citations